CURRENT TRENDS IN TPACK RESEARCH IN ENGLISH LANGUAGE EDUCATION: A SYSTEMATIC REVIEW OF LITERATURE FROM 2017 TO 2021 - Lim Pei Sing; Wardatul Akmam Din; Nik Zaitun Nik Mohamed; Suyansah Swanto (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In this 21st century, traditional ways of teaching and learning have been changed with the evolution of technology. Technological Pedagogical Content Knowledge (TPACK) is one of the conceptual models developed by researchers to facilitate teachersâ€™ professional development. It is believed that TPACK should be developed and mastered by teachers to achieve effective implementation of technology in teaching and learning. This systematic literature review aims to investigate current trends in TPACK research in English language education literature published between 2017 to 2021. The keywords â€œTechnological Pedagogical Content Knowledgeâ€, â€œTPACKâ€, â€œEnglish languageâ€, â€œESLâ€, â€œEFLâ€ and â€œEnglish teachersâ€ with some modifications using â€œANDâ€ and â€œORâ€ were used to obtain relevant articles from Scopus and ProQuest databases. The study inclusion process was done following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020â€™s framework. There were 14 articles yielded and included in this systematic literature review. The results show that TPACK studies in English language education were carried out worldwide. Moreover, half of the reviewed studies used pre-service English language teachers as the participants while others used in-service or both of them. Meanwhile, some studies used English language learners as the participants. In addition, there are a variety of methods including quantitative, qualitative and mixed method employed by the researchers of reviewed studies. We also identified 5 key emerging themes of the reviewed studies including measurement of TPACK level (64%), the relationship between TPACK and other variables (29%), strategy to develop TPACK (29%), implementation of TPACK (14%) and development of TPACK instrument (21%). This paper implies researchers in the English language education field, especially in Malaysia. Further studies on TPACK need to be conducted due to the limited current research in Malaysia.